Feminist literary criticism as an act of subjectivation - Nora Dominguez (Estudios de Teoría Literaria, 2021)
This work follows the critical path developed in different essays of personal production related to the reflection gender studies and its articulation with literature. It proposes how the ways of reading are linked to subject positions and forms of subjectivation relatives to different subjective instances. A second part referes to the critical and theoretical production of Nelly Richard to locate specific debates such as that of “feminine writing” to highlight that its persistence or return reveals how collective appropriations produce a politicization of certain terms.